Interpersonal Behavior: More vs. Less Favorable Teachers - Hajar Ghafarpour; Ahmad Moinzadeh (Journal of English Language Teaching and Learning, 2021)
Classrooms can be regarded as dynamic systems in which behaviors of teachers and students affect each other mutually and in a spiral manner. In this study it was intended to investigate differences in interpersonal behaviors of a more vs. a less favorable teacher at micro- and macro-levels. To analyze classroom interaction dynamically and in real-time, State Space Grid technique was applied. On the macro-level, teacher profiles were determined based on vector method. 211 students of six classes rated the behavior of their own teacher and an imaginary ideal one. One teacher who was closest to and one farthest from that ideal were identified and their classes were video-taped. Two raters coded behaviors with a joystick and then content and structure of interaction were analyzed. Differences on the micro-level were especially noticeable in the strength of attractors, not in their position. Structurally, the behavior of the more favorable teacher had higher variability and less predictability. On the macro-level, the more favorable teacher had Authoritative, and the less favorable one had Directive profiles. The results of this study can be used in promoting interactive ground of the class and in teacher education programs.